Social choice among complex objects - Luigi Marengo; Simona Settepanella (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2010)
We present a geometric model of social choice when the latter takes place among bundles of interdependent elements, that we will call objects. We show that the outcome of the social choice process is highly dependent on the way these bundles are formed. By bundling and unbundling the same set of constituent elements an authority has the power of determine the social outcome. We provide necessary and sufficient conditions under which a social outcome may be a local or global optimum for a set of objects, and we show that, by appropriately redefining the set of objects, intransitive cycles may be broken and the median voter may be turned into a loser.
Keywords: D03; D71; D72; 330; social choice; object construction power; agenda power; intransitive cycles; median voter